A switch in pdgfrb+ cell-derived ECM composition prevents inhibitory scarring and promotes axon regeneration in the zebrafish spinal cord - Tsata, Vasiliki; Schweitzer, Christine; Kolb, Julia; Moeckel, Conrad; Boehm, Benjamin; Rosso, Gonzalo; Lange, Christian; Lesche, Mathias; Hammer, Juliane; Kesavan, Gokul; Beis, Dimitris; Guck, Jochen; et al. (Developmental Cell, 2021)
In mammals, perivascular cell-derived scarring after spinal cord injury impedes axonal regrowth. In contrast, the extracellular matrix (ECM) in the spinal lesion site of zebrafish is permissive and required for axon regeneration. However, the cellular mechanisms underlying this interspecies difference have not been investigated. Here, we show that an injury to the zebrafish spinal cord triggers recruitment of pdgfrb+ myoseptal and perivascular cells in a PDGFR signaling-dependent manner. Interference with pdgfrb+ cell recruitment or depletion of pdgfrb+ cells inhibits axonal regrowth and recovery of locomotor function. Transcriptional profiling and functional experiments reveal that pdgfrb+ cells upregulate expression of axon growth-promoting ECM genes (cthrc1a and col12a1a/b) and concomitantly reduce synthesis of matrix molecules that are detrimental to regeneration (lum and mfap2). Our data demonstrate that a switch in ECM composition is critical for axon regeneration after spinal cord injury and identify the cellular source and components of the growth-promoting lesion ECM.In mammals, perivascular cells impede axon regeneration after spinal cord injury through secretion of an inhibitory ECM. Tsata et al. show that in the regeneration-competent zebrafish, myoseptal and perivascular cells promote axon regeneration by depositing a growth-promoting ECM that is deprived of growth-inhibitory matrix molecules.
CRIS-Team Scopus Importer:2022-08-03
Keywords: axon; ECM; fibroblast; myoseptal cells; optoablation; PDGFRβ; perivascular cells; regeneration; spinal cord; zebrafish

Estimation of the mass density of biological matter from refractive index measurements - Möckel, Conrad; Beck, Timon; Kaliman, Sara; Abuhattum, Shada; Kim, Kyoohyun; Kolb, Julia; Wehner, Daniel; Zaburdaev, Vasily; Guck, Jochen (Biophysical Reports, 2024)
The quantification of physical properties of biological matter gives rise to novel ways of understanding functional mechanisms. One of the basic biophysical properties is the mass density (MD). It impacts the dynamics in sub-cellular compartments and plays a major role in defining the opto-acoustical properties of cells and tissues. As such, the MD can be connected to the refractive index (RI) via the well known Lorentz–Lorenz relation, which takes into account the polarizability of matter. However, computing the MD based on RI measurements poses a challenge, as it requires detailed knowledge of the biochemical composition of the sample. Here we propose a methodology on how to account for assumptions about the biochemical composition of the sample and respective RI measurements. To this aim, we employ the Biot mixing rule of RIs alongside the assumption of volume additivity to find an approximate relation of MD and RI. We use Monte–Carlo simulations and Gaussian propagation of uncertainty to obtain approximate analytical solutions for the respective uncertainties of MD and RI. We validate this approach by applying it to a set of well-characterized complex mixtures given by bovine milk and intralipid emulsion and employ it to estimate the MD of living zebrafish (Danio rerio) larvae trunk tissue. Our results illustrate the importance of implementing this methodology not only for MD estimations but for many other related biophysical problems, such as mechanical measurements using Brillouin microscopy and transient optical coherence elastography.<br
Keywords: Mass density; Refractive index; Optical diffraction tomography; Brillouin microscopy; Optical coherence elastography

Mechanical spinal cord transection in larval zebrafish and subsequent whole-mount histological processing - John, Nora; Kolb, Julia; Wehner, Daniel (STAR Protocols, 2022)
Zebrafish regenerate their spinal cord after injury, both at larval and adult stages. Larval zebrafish have emerged as a powerful model system to study spinal cord injury and regeneration due to their high optical transparency for in vivo imaging, amenability to high-throughput analysis, and rapid regeneration time. Here, we describe a protocol for the mechanical transection of the larval zebrafish spinal cord, followed by whole-mount tissue processing for in situ hybridization and immunohistochemistry to elucidate principles of regeneration. For complete details on the use and execution of this protocol, please refer to Wehner et al. (2017) and Tsata et al. (2021).
CRIS-Team Scopus Importer:2022-05-20
Keywords: Developmental biology; Microscopy; Model Organisms; Neuroscience

Nonlinear dynamics of femtosecond laser interaction with the central nervous system in zebrafish - Jun, Soyeon; Herbst, Andreas; Scheffter, Kilian; John, Nora; Kolb, Julia; Wehner, Daniel; Fattahi, Hanieh (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
Understanding the photodamage processes driven by the complex nonlinear interactions of femtosecond laser pulses within the second tissue transparency window is pivotal for developing novel label-free microscopy techniques. In this research, we identify two distinct cavitation mechanisms produced by 1030 nm femtosecond pulses in the zebrafish central nervous system. The damage remains highly localized for irradiation at lower laser repetition rates, resulting from plasma-induced ablation and localized heating. In contrast, higher laser repetition rates lead to more extensive damage mediated by plasma-induced photochemical reactions. We also investigate how fluorescence labels, involving both linear and nonlinear absorption pathways, influence the dynamics of the photodamage. To confirm our findings, we analyzed cell death and tissue responses to laser-induced injury, including the activation of fibroblasts and the recruitment of immune cells.
CRIS-Team Scopus Importer:2025-05-16
Keywords: central nervous system; deep-tissue imaging; femtosecond pulses; light tissue interaction; photodamage; photothermal damage; phototoxicity; reactive oxygen species; zebrafish

Nonlinear dynamics of femtosecond laser interaction with the central nervous system in zebrafish - Jun, Soyeon; Jun, Soyeon; Herbst, Andreas; Herbst, Andreas; Scheffter, Kilian; John, Nora; Kolb, Julia; Wehner, Daniel; Fattahi, Hanieh (Communications Physics, 2024)
Understanding the photodamage mechanism underlying the highly nonlinear dynamic of femtosecond laser pulses at the second transparent window of tissue is crucial for label-free microscopy. Here, we report the identification of two cavitation regimes from 1030 nm pulses when interacting with the central nervous system in zebrafish. We show that at low repetition rates, the damage is confined due to plasma-based ablation and sudden local temperature rise. At high repetition rates, the damage becomes collateral due to plasma-mediated photochemistry. Furthermore, we investigate the role of fluorescence labels with linear and nonlinear absorption pathways in optical breakdown. To verify our findings, we examined cell death and cellular responses to tissue damage, including the recruitment of fibroblasts and immune cells after irradiation. These findings contribute to advancing the emerging nonlinear optical microscopy techniques and provide a strategy for inducing precise, and localized injuries using near-infrared femtosecond laser pulses.
CRIS-Team Scopus Importer:2024-05-31

Small leucine-rich proteoglycans inhibit CNS regeneration by modifying the structural and mechanical properties of the lesion environment - Kolb, Julia; Tsata, Vasiliki; John, Nora; Kim, Kyoohyun; Möckel, Conrad; Rosso, Gonzalo; Kurbel, Veronika; Parmar, Asha; Sharma, Gargi; Karandasheva, Kristina; Abuhattum, Shada; Lyraki, Olga; et al. (Nature Communications, 2023)
Extracellular matrix (ECM) deposition after central nervous system (CNS) injury leads to inhibitory scarring in humans and other mammals, whereas it facilitates axon regeneration in the zebrafish. However, the molecular basis of these different fates is not understood. Here, we identify small leucine-rich proteoglycans (SLRPs) as a contributing factor to regeneration failure in mammals. We demonstrate that the SLRPs chondroadherin, fibromodulin, lumican, and prolargin are enriched in rodent and human but not zebrafish CNS lesions. Targeting SLRPs to the zebrafish injury ECM inhibits axon regeneration and functional recovery. Mechanistically, we find that SLRPs confer mechano-structural properties to the lesion environment that are adverse to axon growth. Our study reveals SLRPs as inhibitory ECM factors that impair axon regeneration by modifying tissue mechanics and structure, and identifies their enrichment as a feature of human brain and spinal cord lesions. These findings imply that SLRPs may be targets for therapeutic strategies to promote CNS regeneration.<br
Keywords: Biophysics; Mechanisms of disease; Spinal cord injury